2022
DOI: 10.3389/fpubh.2022.928065
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to COVID-19 Health Products in Low-and Middle-Income Countries During the COVID-19 Pandemic: A Rapid Systematic Review and Evidence Synthesis

Abstract: IntroductionThe coronavirus disease 2019 (COVID-19) pandemic has intensified the urgency in addressing pressing global health access challenges and has also laid bare the pervasive structural and systemic inequities that make certain segments of society more vulnerable to the tragic consequences of the disease. This rapid systematic review analyses the barriers to COVID-19 health products in low-and middle-income countries (LMICs). It does so from the canon of global health equity and access to medicines by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 128 publications
1
22
0
Order By: Relevance
“…Finally, our study findings suggest that the country of residence may be a moderating factor for access to health care, medications and access to alternative medical care services. We observed that people who reside in LICs may not only had challenges accessing healthcare and obtaining medications [51,52] but also seem more likely not be able to use alternative medical care services. Though people in HICs had challenges with accessibility to healthcare services during the COVID-19 pandemic [32] the study results indicates that they had less challenges with access to healthcare when compared with LICs and UMICs; obtaining medications when compared with LICs, LMICs and UMICs; and use of alternative medical care when compared with LICs and LMICs during the first wave of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 86%
“…Finally, our study findings suggest that the country of residence may be a moderating factor for access to health care, medications and access to alternative medical care services. We observed that people who reside in LICs may not only had challenges accessing healthcare and obtaining medications [51,52] but also seem more likely not be able to use alternative medical care services. Though people in HICs had challenges with accessibility to healthcare services during the COVID-19 pandemic [32] the study results indicates that they had less challenges with access to healthcare when compared with LICs and UMICs; obtaining medications when compared with LICs, LMICs and UMICs; and use of alternative medical care when compared with LICs and LMICs during the first wave of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 86%
“…The sample composition affected the number of M. tuberculosis reads and depended on the amount of human and bacterial DNA in the sample ( Votintseva et al, 2017 ). Although, the use of certain commercial extraction kits can reduce the turnaround time and are easier to standardize and validate ( Votintseva et al, 2017 ), they are usually more costly and might not be suitable for low- and middle-income settings where there is unavailability or inaccessibility of certain kits/reagents ( Boro and Stoll, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that saponin followed by DNase I treatment depletes Gram-negative bacteria. Saponin treatment combined with a DNase I step is an efficient option to deplete host DNA ( Bachmann et al, 2018 ; Charalampous et al, 2019 ; Boro and Stoll, 2022 ), however, the effect on different bacterial species varies depending on the study. In a study optimizing culture-independent genome sequencing, saponin treatment resulted in almost undetectable levels of human DNA with minimal loss of Bordetella pertussis DNA ( Fong et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…12 One of the causes for this disparity of numbers is the lack of reagents and equipment due either to the lack of affordability or to supply chain disruptions. 13 Reverse transcription polymerase chain reaction (RT-PCR) assays were the gold-standard for SARS-CoV-2 testing but require trained staff and sophisticated laboratory facilities. Lateral ow assays (LFAs) have been developed as a rapid mass screening alternative.…”
Section: Introductionmentioning
confidence: 99%